1965
DOI: 10.1177/004051756503500906
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Changing Humidity on the Insulation of Hygroscopic Clothing

Abstract: Two series of experiments are described in which the insulation walue of wool fabrics is measured during the process of sorption or desorption by the fabric. The results are discussed from the point of view of the buffering action of clothing made from hygroscopic fibers. The buffering effect predicted in 1941 by Cassie et al. has been detected in a physical, as distinct from physiological, experiment, but only 30% to 50% of the total sorption heat is effective in reducing heat loss through the fabric. These m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

1995
1995
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 5 publications
(1 reference statement)
0
4
0
Order By: Relevance
“…The thermal insulation under transient conditions is related to the concept of heat of sorption, which influences the thermal insulation value of the garments and the thermal sensation to the wearer under dynamic wear situations. David (1964David ( ,1965 [151,194] investigated the thermal buffering ofclothing by conducting a series of experiments. He found that 30% to 50% ofthe total sorption heat released was effective in reducing the heat loss through the fabric.…”
Section: Warmthmentioning
confidence: 99%
“…The thermal insulation under transient conditions is related to the concept of heat of sorption, which influences the thermal insulation value of the garments and the thermal sensation to the wearer under dynamic wear situations. David (1964David ( ,1965 [151,194] investigated the thermal buffering ofclothing by conducting a series of experiments. He found that 30% to 50% ofthe total sorption heat released was effective in reducing the heat loss through the fabric.…”
Section: Warmthmentioning
confidence: 99%
“…Spencer-Smith (1976, 1978 developed part of the theory involved for fabrics, but restricted his studies to physical measurements, as did Farnworth (1986), applying a more sophisticated mathematical model. 0014 David (1965) was the first to report the effects of absorption in clothing ensembles, using a thermal manikin. He too found long-lasting effects.…”
Section: Introductionmentioning
confidence: 99%
“…Another separate but related possible contributor to differences among bedding products constructed of wool and other fills is their exothermic heat of sorption as a result of absorption of water vapor. 9,26,28 Conceptually, the heat of sorption of water vapor by fibers can be split into two components: the latent heat of condensation as water changes from vapor to liquid (approximately 2.5 kJ per gram of water) and the heat of sorption as the liquid is absorbed. 27,[29][30][31] The heat of sorption from liquid is a function of regain, which in the case of wool varies between 0 and 1 kJ per gram of water.…”
mentioning
confidence: 99%